Magnetized drinking water improves productivity and blood parameters in geese - El-Hanoun, Ali M.; Attia, Youssef A.; Al-Harthi, Mohammed A.; Habiba, Hany I.; Oliveira, Maria C. (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: Quality of drinking water is an issue that imposes limits on animal farming. Improving water quality can be a solution to animal farming and to the enhancement of animal production in areas with limited water supplies. Objective: To evaluate the effect of water quality and magnetized water on productivity and blood parameters of Egyptian geese. Methods: One hundred and eight (108) Egyptian geese were randomly distributed among four water treatments in a 2×2 factorial design that included two types of water (tap water and well water) and exposure or non-exposure to magnetized tap water and magnetized well water. Results: Well water was of poor quality. Geese consuming this water exhibited lower productive and reproductive performance, lower progesterone and estrogen levels, impaired renal and liver functions and lower total antioxidant capacity. Their eggs had lower weight, lower yolk percentage, and reduced shell thicknesses. The magnetic treatment improved the quality of both types of water, with a greater effect on well water. Magnetized water increased water consumption and performance of geese, along with improved renal and liver functions, reproductive hormones, and antioxidant status. Magnetized water improved growth performance, dressing percentage of goslings, and the amount of meat produced. Conclusion: Magnetized tap water improved body weight and feed conversion rate, besides renal and hepatic functions. It also increased production, quality and hatchability of eggs, and levels of reproductive hormones (i.e. progesterone and estrogen), and the antioxidant status in blood.